Does geopolitical risks drive the extreme spillovers of bulk energy and chemical commodity - Zhang Tao; Tianzhuang Li; Yadi Chen; Xiaoyue Huang (PLoS ONE, 2025)
Geopolitical risks (GPR) can affect the prices of natural resources, which are crucial for survival and sustainable economies. Based on the TVP-VAR-BK models, this paper examines the asymmetric risk contagion between geopolitical risk, bulk energy, and chemical commodity from a time-frequency perspective. The results show that the risk contagion of geopolitical risks, bulk energy and chemical commodity markets has time-varying asymmetry and periodicity, and is susceptible to extreme events. Furthermore, the main driving factor is high-frequency spillover, which has “short-term fragility”, that is, the risk spillover in the short term is more significant than in the medium and long term, and network spillover is mainly caused by negative risk changes. In addition, the bulk energy market is the main risk transmitter, while the chemical commodity market is the main risk receiver. The risk contagion of crude oil on bitumen markets is the most significant. Finally, as a downstream market of the crude oil industry, the chemical commodity market not only directly accepts risk contagion from the crude oil market, but also transmits risks along the “bulk energy - geopolitical risk - chemical commodity” path. This evidence has important implications for governments and regulators in taking steps to prevent extreme spillover effects and a series of chain reactions from geopolitical risks.